Abordagem de manutenção centrada em confiabilidade: estudo de caso em um ponto de entrega de gás natural de uma empresa de transporte de petróleo - Lannes Junior, Ayr (2009)
The current paper was undertaken aiming to present case studies, based in the evaluation of a proposition structured maintenance management under the light of process safety, using risk assessment and knowledge management, with the purpose of support the elaboration of maintenance plans and cost reduction. The proposal demonstrates that the risks of maintenance and activity risks were properly considered and treated. As methodological option, it was chosen the development of case studies; the intended results being align the challenges of the continuous improvement of maintenance, of the operation of assets and of the acquired knowledge management, in compliance with the company strategic directives and minimization of the costs related to the operation of Natural Gas custody transference facilities. It was verified that the application of maintenance centered in reliability as a tool of rationalization of preventive maintenance plans, ally the traceability of its foundations, resulted, in gains of productivity and quality with reduced global costs of maintenance